Four ear tags evaluated - Sprott, L.R.; Corah, L.R. (Kansas State University. Agricultural Experiment Station, 2011)
Four types of ear tags were evaluated for retention over 2 years. Retention was low for one type, and high for the other three types.
Keywords: Beef; Ear tags